2021
DOI: 10.1210/clinem/dgab075
|View full text |Cite
|
Sign up to set email alerts
|

HDL Particle Subspecies and Their Association With Incident Type 2 Diabetes: The PREVEND Study

Abstract: Background and aims High-density lipoproteins (HDL) may be protective against type 2 diabetes (T2D) development, but HDL particles vary in size and function which could lead to differential associations with incident T2D. A newly developed nuclear magnetic resonance (NMR)-derived algorithm provides concentrations for seven HDL subspecies. We aimed to investigate the association of HDL particle subspecies with incident T2D in the general population. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 65 publications
1
34
0
Order By: Relevance
“…Furthermore, HDL particles are able to affect β-cell function [20,73], and HDL-C makes part of established diabetic risk models [74,75]. Recently, HDL size was found to be associated with incident T2D even independent of HDL-C [26]. In the current study, we therefore adjusted HDL-C or alternatively for HDL size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, HDL particles are able to affect β-cell function [20,73], and HDL-C makes part of established diabetic risk models [74,75]. Recently, HDL size was found to be associated with incident T2D even independent of HDL-C [26]. In the current study, we therefore adjusted HDL-C or alternatively for HDL size.…”
Section: Discussionmentioning
confidence: 99%
“…Lipoprotein parameters were measured by NMR LipoProfile ® testing at Labcorp (Morrisville, NC). NMR spectra were collected on an optimized version of the NMR LipoProfile test (LP4 algorithm) [22,26,30]. Very large, large, medium, small, and very small triglyceride rich lipoprotein particles (TRLP) and large, medium, and small LDL particles (LDLP) were quantified using the conventional deconvolution method and the amplitudes of their spectroscopically distinct lipid methyl group NMR signals [31].…”
Section: Clinical and Laboratory Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past two decades, metabolomics has been widely utilized in large epidemiological studies, and some metabolites/pathways have been identified and validated to be associated with insulin metabolism or being predictive of diabetes across different studies [ 35 ]. Table 2 summarizes the findings from some of key prospective studies [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 ].…”
Section: Metabolomics In Diabetesmentioning
confidence: 99%
“…Twenty-three out of the thirty-two biomarkers have already been reported to be useful in the calculation of MD as proxy of homeostasis loss (Supplemental Table 2) [16]. We replaced HDL cholesterol, used in a previous report [16], with seven HDL subspecies that have lately been reported to be differently associated with the risk of T2D [32]. Additionally, BCAA (valine, leucine, isoleucine) were included in the analysis because of their association with T2D [15], which has been shown to be causal [33].…”
Section: Mahalanobis Distancementioning
confidence: 99%